The haemagglutination activity of equine herpesvirus type 1 glycoprotein C - Andoh, Kiyohiko; Hattori, Shiho; Mahmoud, Hassan Y.A.H.; Takasugi, Maaya; Shimoda, Hiroshi; Bannai, Hiroshi; Tsujimura, Koji; Matsumura, Tomio; Kondo, Takashi; Kirisawa, Rikio; Mochizuki, Masami; Maeda, Ken (Virus Research, 2015)
•Equine herpesvirus type 1 (EHV-1) glycoprotein C (gC) has haemagglutination (HA) activity for equine red blood cells (RBCs).•The HA activity was inhibited by addition of MAbs against gC, but not inhibited by addition of heparin.•This is the first report of a heparin-insensitive HA activity associated with a herpes viral gC protein. Equine herpesvirus type 1 (EHV-1) has haemagglutination (HA) activity toward equine red blood cells (RBCs), but the identity of its haemagglutinin is unknown. To identify the haemagglutinin of EHV-1, the major glycoproteins of EHV-1 were expressed in 293T cells, and the cells or cell lysates were mixed with equine RBCs. The results showed that only EHV-1 glycoprotein C (gC)-producing cells adsorbed equine RBCs, and that the lysate of EHV-1 gC-expressing cells agglutinated equine RBCs. EHV-1 lacking gC did not show HA activity. HA activity was inhibited by monoclonal antibodies (MAbs) specific for gC, but not by antibodies directed against other glycoproteins. In addition, HA activity was not inhibited by the addition of heparin. These results indicate that EHV-1 gC can bind equine RBCs irrespective of heparin, in contrast to other herpesvirus gC proteins.